THE ROLE OF DIGITAL MARKETING IN ENHANCING TOURISM BUSINESS MARKETING NETWORKS IN PULO ACEH - Putri Mauliza; Juwita Juwita; Marlina Marlina; Susanti Susanti; Arsyad Arsyad (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
This study explores the role of digital marketing in strengthening the tourism business network in Pulo Aceh. Employing a descriptive qualitative approach, data were collected through interviews, field observations, and literature review. The findings show that social media platforms, online communication applications, and digital storytelling techniques have significantly expanded the promotional reach of tourism destinations and improved connectivity with potential visitors. However, several challenges persist, including limited digital literacy among local communities, unequal internet accessibility, and weak collaboration among stakeholders. The study concludes that digital marketing can serve as a strategic tool to enhance tourism marketing in Pulo Aceh through initiatives such as digital skills training, improvements in information technology infrastructure, and the development of stronger collaborative networks with stakeholders including local government and private sectors. This research contributes theoretically by enriching the discourse on digital-based tourism marketing in remote island regions, while also offering practical insights for stakeholders to optimize digital platforms in promoting tourism destinationsKeywords: Authors should select a maximum of five keywords that are specific and reflect what is essential about the article.